Income Generation from Library Buildings:the UK Experience - Bulpitt, Graham (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
This paper has been prepared to contribute to the financial theme of the Warsaw Conference by considering ways in which library buildings may be used to generate income, drawing on the experience of a number of university libraries in the United Kingdom. Although almost all libraries generate income, it is often difficult to identify income generation activities which are based on buildings as a physical resource and experience here is much more limited.